STRATEGI PEMASARAN AGROINDUSTRI KOPI BUBUK PT. MIYOGA DI DESA SIPATUHU KECAMATAN BANDING AGUNG KABUPATEN OGAN KOMERING ULU SELATAN - Yudi Hartono, Munsiarum, (JASEP, 2024)
Marketing problems can arise from within or outside the environment of a business, so a strategy is needed so that marketing goals can be achieved. The purpose of this study was to analyze the marketing strategy of ground coffee produced by PT. Miyoga. This research was conducted in Sipatuhu Village, Banding Agung District, South OKU Regency. The location of the study was chosen deliberately, namely by considering that in Sipatuhu Village, Banding Agung District, South OKU Regency, there is an agro-industrial company that processes coffee beans into ground coffee, namely PT. Miyoga. This study uses a case study method, where PT. Miyoga is the case unit. The results of the study show that the internal factors of the ground coffee agro-industry of PT. Miyoga include 1) strengths consisting of quality products with a distinctive taste, durable products, production of various variants of ground coffee, direct and online marketing, and products that already have certificates; and 2) weaknesses consisting of less than optimal promotion, less than optimal capital, less than strategic location, and inadequate IT HR qualifications. While external factors include 1) opportunities, consisting of population growth, wide market share, development of IT technology, government support, and easy access to raw materials; and 2) threats, consisting of competitors, changes in weather and climate conditions, middlemen, and price increases for goods and services. The results of the SWOT analysis show that the marketing strategy implemented is an aggressive strategy, or S-O, namely: improving the quality, uniqueness, and diversity of products; utilizing modern technology; optimizing the production of ground coffee produced; maintaining good relations with partner farmers, customers, and also with the government; and improving the quality of raw materials, supervision, and packaging so that the product can last a long time.